INVESTIGATING IMPLICATURE IN ILLOCUTIONARY ACTS EMPLOYED BY MUSEUM GUIDE AND ENGLISH SPEAKING TOURISTS - Ginanjar Legiansyah; Ida Zuraida Supri (Universitas Widyatama, 2020)
This research aims at identifying types of implicature and analyzing types speech acts and the strategies employed by the speakers and hearers during the visit at the Museum Asian African Conference. The method used in this research is qualitative descriptive analysis, where the data is collected, then sorted and categorized and finally analyzed based on the theory. The results show that 1) two types of implicatures are found; conversational implicature (91%) and conventional implicature (9%), 2) Four types of illocutionary acts encountered in the conversation; assertive (90%), directive (6%) commissive (93%) and expressive (1%) and 3) Both strategies are used in delivering illocutionary acts; direct strategies (94%) is more dominant than the indirect one (6%).